Memilih Untuk Tidak Memilih: Protest Voting Dalam Pemilu Lokal di Kabupaten Lebak, Banten - Mahpudin Mahpudin (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2021)
This article discusses protest voting in the context of regional elections, which contest between a single pair of candidates against an empty box. Empty box is presented to provide alternative options to citizens who are not interested in choosing a pair of candidates. This article argues that the empty box becomes an instrument for voters to protest. Using the case of the Lebak local election in 2018, this article seeks to find answers to the question of why some voters are interested in choosing an empty box, what is the main object of the protest, and how the protest was carried out. This type of qualitative research with a case study approach was chosen as the research method. Data collection was carried out through in-depth interviews and literature studies. The findings show that the empty box is an instrument for the people in South Lebak, especially Malingping District, to express their dissatisfaction with the candidate, Iti Octavia Jayabaya. On the other hand, protest voting using empty boxes keeps its dilemmas and paradoxes. Some protesting voters continued to express their dissatisfaction by selecting candidate pairs for fear of intimidation and other reasons.